A Bourdieusian analysis exploring the meaning of sport for young women from refugee backgrounds in an Australian state high school. Issue 2 (12th February 2021) - Harwood, Georgie; Sendall, Marguerite C.; Heesch, Kristiann C.; Brough, Mark
ABSTRACT: For young people from refugee backgrounds, schools are often a critical part of their resettlement experience. Currently, there is a lack of research about the role of sport within the Australian school environment in helping these young people address resettlement challenges. Research on community sport suggests that sport can be a significant and effective platform for introducing young people from refugee backgrounds to Australian society during the resettlement process. School sport may play a similar role. Drawing on ethnographic fieldwork over a 12 month period, this paper explores the meaning of sport for young women from refugee backgrounds who were students (in years 7–12) at a publicly-funded state high school in Brisbane. A Bourdieusian theoretical framework was used to guide the need for critical awareness of the workings of power in the school environment. The findings show how sport creates tensions of habitus as students must balance their desire to participate in sport against competing sets of values and dispositions toward sport. The gendered nature of sport further complicated this tension in the way it structured different opportunities for participation in sport between young women and men. Our findings suggest the need for a more deliberate reflexive consciousness to inform the practices of educators and policymakers to ensure sport is both inclusive and culturally safe.